RIYANTO DAN BOM NATAL 2000 : NALAR BANSER NU DALAM NESTAPA KETAHANAN TOLERANSI BERAGAMA DI INDONESIA - Sujono, Imam (JURNAL ISLAM NUSANTARA, 2021)
In the holy book of the Qur’an there is Surat Al-Kafirun verse 6, which reads "lakum diinukum wa liyadiin," which means "For you your religion, and for me my religion." In this letter it is sufficient to show how tolerance is in religion. The research examines issues that focus on (1) What is the Reasoning for the Tolerance of the NU Banser? (2) Why did the death of Riyanto in the Praxis of Religious Tolerance during Christmas Celebration at Eben Haezar Mojokerto Church in 2000? This research uses field studies and literature reviews with an empirical and historical sociological approach. From the results obtained the following answers: (1) NU Banser understands Ahlussunnah Wal Jamaah and there is tasamuh which is seen as Ukhuwah Insaniyah (humanity) and Ukhuwah Wathaniyah (nationalism) which are the basic principles of tolerance for religious diversity, so that NU and BANSER always trying to create, maintain, maintain tolerance for religious diversity, (2) BANSER Riyanto was in charge of safeguarding the 2000 Christmas celebration at the Eben Haezar Mojokerto Church and died along with a bomb explosion to save the Christmas congregation.